1949
DOI: 10.1021/ja01171a094
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of DL-Threonine. II. Interconversion of DL-Threonine and DL-Allothreonine

Abstract: In connection with a search for more practical syntheses of DL-threonine, useful methods of converting the more readily available DL-allothreonine into its epimer were sought. A method of effecting the inversion was discovered and announced in a preliminary communication.3 While that paper was in press a report43 in the recent British literature on the same subject reached this country, and was followed later by a second article.415 We wish to elaborate at this time our previous communication on the method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1956
1956
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Inversion of configuration at the P-position of P-hydroxy-a-amino acids can usually be accomplished via the oxazoline (25,26). However, attempts to prepare an oxazoline by treating N-benzoyl-DL-erythro-P-hydroxyisoleucine methyl ester with thionyl chloride under the appropriate conditions gave back the starting material.…”
mentioning
confidence: 99%
“…Inversion of configuration at the P-position of P-hydroxy-a-amino acids can usually be accomplished via the oxazoline (25,26). However, attempts to prepare an oxazoline by treating N-benzoyl-DL-erythro-P-hydroxyisoleucine methyl ester with thionyl chloride under the appropriate conditions gave back the starting material.…”
mentioning
confidence: 99%
“…The intermediacy of 2 ~ was, however, de~i~onstrated by t.l.c., and it was confirmed that under the hydrolysis conditions (0.8 N hydrochloric acid in aqueous ethanol) isomerization of 2 to 3 was rapid and efficient. The same zster 3 could also be obtained from the trans-isomer 5 of the alcohol 2, though not under such mild conditions, the use of thionyl chloride o r concentrated sulfuric acid being necessary, in which case the yield was quantitative. …”
mentioning
confidence: 89%
“…The conversion of 5 into 3 is in fact an example of a well established reaction type in which an a-acylamino alcohol is transformed by acidic reagents (most frequently thionyl chloride) into a derivative of the amino alcohol with inversion at the carbinol carbon (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The key step is the formation of an oxazolinium cation by S,2 attack of the acylamino oxygen.'…”
Section: Cophmentioning
confidence: 99%
See 2 more Smart Citations